1972
DOI: 10.1111/j.1399-6576.1972.tb00572.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Metabolic Responses to Halogenated Anaesthetics

Abstract: Halogenated ethers, as well as halothane, cause an appreciable rise in plasma norepinephrine and, perhaps, in plasma epinephrine. The technique of measurements of the biogenic amines in plasma is not sensitive enough to obtain clear‐cut comparative data. Nevertheless, the changes are evidently less marked than those occurring with “balanced” anaesthetic techniques. No significant metabolic alteration occurs with the fluorinated ethers except for a rise in blood sugar and plasma cortisol. This probably reflects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1973
1973
1982
1982

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Although some investigations have not demonstrated significant plasma catechol- 23 24 amine changes with isoflurane, ' these studies mainly used dogs and the variance in results may relate to the differences in cardiovascular responses between dog and man. On the other hand, Dobkin, et al 25 reported increased cateeholamine levels in non-cardiac patients following isoflurane anaesthesia. They found norepinephrine levels to be increased more than epinephrine.…”
Section: -mentioning
confidence: 99%
“…Although some investigations have not demonstrated significant plasma catechol- 23 24 amine changes with isoflurane, ' these studies mainly used dogs and the variance in results may relate to the differences in cardiovascular responses between dog and man. On the other hand, Dobkin, et al 25 reported increased cateeholamine levels in non-cardiac patients following isoflurane anaesthesia. They found norepinephrine levels to be increased more than epinephrine.…”
Section: -mentioning
confidence: 99%